2017
DOI: 10.1093/ofid/ofx163.1235
|View full text |Cite
|
Sign up to set email alerts
|

Foley Catheter with Peri-Urethral Antimicrobial Irrigation for the Prevention of Catheter Associated Urinary Tract Infections – Assessment in an In Vitro Model

Abstract: BackgroundCatheter associated urinary tract infections (CAUTIs) are a significant medical issue with substantial morbidities and costs. CAUTIs are primarily caused by colonization of the external surface of Foley catheters which serve as conduits for colonizing microbes to access the bladder. In order to prevent these CAUTIs, we developed a double-cuff Foley catheter with a novel irrigation cuff for daily irrigation of the periurethral space with a biocompatible antimicrobial disinfecting solution. This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Essentially, four models of the urinary tract or sections of the urinary tract and their adaptations have been developed in an attempt to more closely represent the anatomy and conditions in situ [ 28 , 44 46 ]. These models are the bladder model by Stickler et al [ 86 ], the urinary tract model by Gaonkar et al [ 2 ], the CAUTI model by Rosenblatt et al [ 87 ], and the meatus model by Holland and Fish [ 39 ].…”
Section: Microbial In Vitro Catheter Testing Anmentioning
confidence: 99%
See 1 more Smart Citation
“…Essentially, four models of the urinary tract or sections of the urinary tract and their adaptations have been developed in an attempt to more closely represent the anatomy and conditions in situ [ 28 , 44 46 ]. These models are the bladder model by Stickler et al [ 86 ], the urinary tract model by Gaonkar et al [ 2 ], the CAUTI model by Rosenblatt et al [ 87 ], and the meatus model by Holland and Fish [ 39 ].…”
Section: Microbial In Vitro Catheter Testing Anmentioning
confidence: 99%
“…Recently, the Gaonkar et al [ 2 ] model has been adapted by Rosenblatt et al [ 90 ]. Communicated on a poster presented in October 2017 at the IDweek conference in San Diego, California, Rosenblatt et al [ 87 ] revealed their modified version of the urinary tract model or CAUTI model ( Figure 6 ). This model consists of only one tube with an upper bulbous end to allow inflation of the retention cuff and a cap at the other end.…”
Section: Microbial In Vitro Catheter Testing Anmentioning
confidence: 99%
“…Numerous studies have been carried out to test new catheter materials, antimicrobials, natural compounds, alternative catheter designs, probiotics and patient care regimes in an effort to reduce or prevent CAUTIs related to indwelling catheters with varying levels of success (Hull et al 2000;Hentzer et al 2002;Stickler et al 2002;Brosnahan et al 2004;Mathur et al 2006;Stickler 2014;Levering et al 2016;Cortese et al 2018). There are several in vitro models to test the efficacy of indwelling catheters to prevent either biofilm formation, encrustation or CAUTI development (Stickler et al 1987;King et al 1992;Morris et al 1997;Stickler et al 1999;Gaonkar et al 2003;Barford et al 2008;Williams and Stickler 2008;Coenye and Nelis 2010;Jordan et al 2015;Chua et al 2017;Rosenblatt et al 2017;Cortese et al 2018). There are two main anatomical in vitro models that have been developed to test indwelling catheters, that is, the bladder model described by Stickler et al (1999Stickler et al ( , 1987 and the urinary tract model developed by Gaonkar et al (2003).…”
Section: Introductionmentioning
confidence: 99%
“…There are two main anatomical in vitro models that have been developed to test indwelling catheters, that is, the bladder model described by Stickler et al (1999Stickler et al ( , 1987 and the urinary tract model developed by Gaonkar et al (2003). Both of these models have been adapted and inspired a multitude of derivative models that have aided in the advancement of indwelling catheter design and CAUTI management (King et al 1992;Morris et al 1997;Barford et al 2008;Williams and Stickler 2008;Jordan et al 2015;Chua et al 2017;Rosenblatt et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Different Foley catheter lock solutions were previously tested, for example ethanol, minocycline alone or in combination with EDTA (Raad et al ) and N‐acetylcysteine (Marchese et al ). Recently, due to the emergence of resistant micro‐organisms to commonly used antibiotics, nonantibiotic antimicrobials and alternative methods to antimicrobial treatments are gaining popularity as promising methods to control infections (Rosenblatt et al ; Noeltinget et al ; Sihra et al ).…”
Section: Introductionmentioning
confidence: 99%